Prospering meaningful learning experience ecosystem via project outcome-based learning (PO-BL): A case study of Malaysian Public University undergraduate students - Omar, Muhd Khaizer; John, Roger; Mat Rashid, Abdullah; Abdullah, Arnida (Advance Scientific Research, 2020)
If there is one thing that students might loath today is the monotonous and stagnant learning process which hinder the harmonious teaching and learning ecosystem. Students have good reasons to reprimand the school at all time, that the exam-oriented has and always become caustic effects of prospering their potential. Because every student comes with their unique traits and characteristics, focusing mainly on objective-based evaluation is not always the best practice. The school lackluster performance has been heavily emphasized on the whole students’ performance; trigger a question of whether the exam-based orientation is the only method of students’ evaluation. Pertaining to the aforementioned issue, this article promotes Project Outcome-Based Learning (PO-BL) as an alternative assessment method in evaluating student learning outcomes and derive reflections from students’ perspectives after participating in PO-BL activities. Forty undergraduate students who enrolled in STE3603 (Manipulative Skills III) course were selected as research subjects. This group of students was chosen after taking part in RoboWars competition in the Faculty of Educational Studies Innovation Showcase organized by the Putra Future Classroom (PFC), Universiti Putra Malaysia. In this competition, students were asked to demonstrate the robot and compete in the battle competition. Analysis, Design, Development, Implementation, and Evaluation (ADDIE model) was adapted to monitor the progress on the robotic project from the first week of classroom practical session to 13th week. The students were then selected to be part of the research project by implying the purposive sampling technique. The subjects were requested to share their personal experiences from the project they did and what the project meant to them via open-ended qualitative questions. The questions were distributed online using ‘JotForm’. We hired expert reviewers to inform the qualitative questions and obtain findings from developed research questions. The responses in narrative forms were downloaded in Excel Spreadsheet and analyzed thematically. The theme that emerged from the study then being matched based on the meaningful learning attributes from previous studies to justify the characteristics. The characteristics from the emergence themes were derived from constant comparative analysis using the color-coded technique. We also triangulated the themes with other data collected prior, during, and after the project completion. The process of triangulation involving data from observation, student report, and lesson plan for one semester. The findings from the study produced imperative contributions of PO-BL from myriad aspects. It is noteworthy to highlight that to reduce the traditional teaching and learning drawbacks, PO-BL might be one of the solutions to enhance the retention of students in the classroom and embrace meaningful learning experience for learners. For the purpose of achieving meaningful learning, PO-BL approach has been useful to engage students in an active, constructive, intentional, authentic and co-operative learning environment which emphasizes on the holistic teaching and learning ecosystem.